(untitled) (Global Journal of Management and Business Research, 2022)
In just few weeks COVID-19 immerses in the world, affecting intimidating the lives and health of millions of people all around the world. The Pandemic also extremely impacted the Hospitality and Tourism industry across the country. Its effect disrupted human lives and pushed the country to an economic slowdown. This Pandemic brought fear of travel and dining out, on every person be it a domestic or an international traveller. Lockdowns and intra state travel ban, and the fear of being quarantined took its toll on Hospitality and Tourism Industry. In This paper researchers are making an effort to find out the extent to which this deadly Virus (COVID-19) has impacted the Travel and Tourism industry in India and also explains how our tourism sector shall cope with this extraordinary circumstance, and establish Management and Recovery strategies. Pre COVID-19, Hotels and Restaurants were relying on various techniques and marketing skills for selling Food and Beverage, but post COVID-19 the entire scenario changed and those skills went redundant. Reinventing and innovative use of technology is the call of the hour to breathe life into the Hospitality and Tourism Industry.